Investigation of the cutting mechanisms and the anisotropic ductility of monocrystalline sapphire. Issue 1 (2017) - Mizumoto, Yuta; Maas, Philipp; Kakinuma, Yasuhiro; Min, Sangkee
Abstract: In this study, plunge-cut tests are conducted on single-crystal sapphire to investigate the brittle and ductile deformation mechanisms from the viewpoint of crystal anisotropy. The anisotropic deformation behaviour of the machined sapphire substrate manifests itself in the critical depth of cut and the diverse crack morphologies. Based on a resolved stress model that is adapted to the experimental procedure, weighted resolved stresses are computed, and the tendency of brittle–ductile transition depending on the peculiarities of the low-symmetry hexagonal crystal structure is discussed. Rhombohedral twinning is assumed to dominate the brittle–ductile transition.